Development Status and Trend of Space Optical Communication Technology - Shaowen LU; Xia HOU; Guotong LI; Jianfeng SUN; Hanghua YU; Weibiao CHEN (天地一体化信息网络)
Based on the laser inter-satellite communication link to realize information transmission between diff erent satellite nodes in satellite constellation, it can solve the problems of slow data rate and limited frequency resources in traditional satellite communication technology.Firstly, the main components of space laser communication technology and the research status at home and abroad were introduced.Then, the technical difficulties and main solutions of high-performance tracking, fast acquisition and high-throughput communication of the terminal were described respectively.Finally, the development trend of space laser communication miniaturization, lightweight and low power consumption technology were described, and the new technology was discussed, which provided relevant reference for the development of space laser communication technology.